A troca de prazeres e dores no ’Fédon’ - Marques, Marcelo (Revista Archai, 2015)
Abstract: In this article, I aim to explore the relation between what is pleasurable and what is painful understood as opposites and the topic of ’exchange as the use of goods whichis guided (or not) by reflective thinking (phronesis) in the Phaedo (60b; 69a-b). On the other hand, I also analyse h some of Antiphon´s fragments (DK87B49, B57-62, among others) in order to discuss the criticism that Socrates addresses to the so called "commerce" between pleasures and pains, hopes and fears. This confrontation helps to clarify the differences between a philosophical way of living and the values that are prevailing among Athenian citizens. Keywords: Plato, Phaedo, Pleasure, Socrates, Antiphon.